Positive association of the DIO2 (deiodinase type 2) gene with mental retardation in the iodine-deficient areas of China. Issue 8 (30th July 2004) - Guo, T-W; Zhang, F-C; Yang, M-S; Gao, X-C; Bian, L; Duan, S-W; Zheng, Z-J; Gao, J-J; Wang, H; Li, R-L; Feng, G-Y; St Clair, D; et al.
Abstract : Background: Iodine deficiency is the commonest cause of preventable mental retardation (MR) worldwide. However, in iodine-deficient areas not everyone is affected and familial aggregation is common. This suggests that genetic factors may also contribute. Thyroid hormone (TH) plays an important role in fetal and early postnatal brain development. The pro-hormone T4 (3, 3′, 5, 5′-triiodothyronine) is converted in the brain to its active form, T3, or its inactive metabolite, reverse T3, mainly by the action of deiodinase type 2 (DIO2). Methods: To investigate the potential genetic contribution of the DIO2 gene, we performed a case-control association study using three common SNPs in the gene ( rs225014, rs225012, and rs225010 ) that were in strong linkage disequilibrium with each other. Results: Single marker analysis showed a positive association of MR with rs225012 and rs225010 . Particularly with rs225012, TT genotype frequency was significantly higher in MR cases than in controls (χ 2  = 9.18, p = 0.00246). When we compared the distributions of common haplotypes, we also found significant differences between mental retardation and controls in the haplotype combination of rs225012 and rs225010 (χ 2  = 15.04, df 2, global p = 0.000549). This association remained significant after Bonferroni correction (p = 0.0016470). Conclusion: We conclude that allelic variation in the DIO2 gene may affect the amount of T3 available and in an iodine-deficient environment may partly determine overall risk of MR.